PENGARUH CUSTOMER SOCIABILITY DAN CUSTOMER SERVICE EXPERIENCE TERHADAP WORD OF MOUTH POSITIF DI RUMAH SAKIT GIGI DAN MULUT TRISAKTI - Rizki Rizki (Jurnal Manajemen dan Pemasaran Jasa, 2015)
Purpose – Since positive word-of-mouth (WOM) is an expression of customer-actualizedvalue, the paper postulate that WOM is not only related to a holistic set of assessments ofthe service experience but also to the idiosyncratic nature of the individual customer. Inparticular, do socially oriented individuals have a greater propensity to engage in positiveWOM? The purpose of this paper is to test hypotheses that customer sociability as well as aset of dimensions of the total service experience, are antecedents of positive WOM. Thecontext studied is a dental treatment involving considerable personal meaning and implicationin the whole service process.Design/methodology/approach – A cohort of 120 patients arestudied post-treatment. Independent variables include the agreeableness and extraversion,other-oriented values, as well as dimensions of the service experience assessed by informationadequacy, pain and discomfort, patient-to-patient interaction, patient-to-personnelinteraction, and recovery outcomes. The dependent variable is the strength of positive WOMintentions.Findings – The sociability of patients as measured by their agreeableness,extraversion and other-oriented values is significantly related to the strength of positiveWOM intentions. Also, to varying degrees, all dimensions of the service experience areassociated with positive WOM intentions.Keywords: Sociability, Customer loyalty, Customer service experience, word of mouth